INTELLIGENT SENSOR FOR ESTIMATING FRACTAL PROPERTIES OF GAS DISCHARGE RADIATION IMAGES OF WATER AND AQUEOUS SOLUTIONS - Glukhova, Natalia; Pesotskaya, Ludmila (Collection of scientific papers «ΛΌГOΣ», 2025)
Modern achievements in the field of information and measurement technologies have provided the possibility of obtaining measurement information with its processing based on the use of intelligent sensors. Today, intelligent sensors are used in various industries to monitor the state of various technological objects and processes